Spent mushroom substrate performance for pyrolysis, steam co-gasification, and ash melting. (February 2021) - Koido, Kenji; Ogura, Toru; Matsumoto, Ryosuke; Endo, Kenji; Sato, Michio
Abstract: Spent mushroom substrate is expected to be utilised as gasification feedstock in the future. This study investigated its performance in pyrolysis, steam co-gasification, and ash melting. During pyrolysis, derivative thermogravimetry showed shoulder curves indicating higher hemicellulose content compared with timber waste. Steam co-gasification was evaluated using a laboratory-scaled fixed-bed downdraft gasifier. The results showed that blending the substrate with Erianthus at a blend rate of 50 wt% enhances carbon conversion to gas and hydrogen by 7.5–8.8% points, with lower H2 S yield due to the formation of CaSO4 on the biomass surface. Furthermore, blending the substrate with Japanese cedar resulted in increased softening and fusion temperature, which is explained by the formation of calcium minerals (e.g., gehlenite and albite–calcian). Based on these results, spent mushroom substrate demonstrates high potential to serve as regional feedstock by co-gasification. Graphical abstract: Image 1 Highlights: Spent mushroom substrate pyrolysis, co-gasification, and ash melting are examined. Derivative thermogravimetry shows shoulder peak due to the hemicellulose content. Co-gasification is effective for enhanced conversion and reduced sulphur yield. Mixing the substrate with the Japanese cedar raises soften and fusion temperatures. The substrate is a potential feedstock by co-gasification in efficiency and melting.